What’s Too Private? Values and Realities in Southeast Asia - Levy , Daniel (International Higher Education, 2020)
A central question raised worldwide by the astonishing growth of private higher education (PHE) is how private is “too private”? The question encompasses both PHE’s enrollment share and PHE’s nature. A key gauge of PHE’s nature is whether PHE is for-profit or nonprofit. Southeast Asia in general, including the Philippines and Vietnam specifically, illustrates some important common, and some intriguing uncommon, responses to the “too private” question.